Comparison of Self-Assessment with Peer and Student Assessment in Evaluating the Overall Performance of the Faculty - Imran Amjad, Syed Shakil-ur-Rehman, Asghar Khan , Khalid Farooq Danish, Ilyas Babar Awan, Sikandar Ghayas Khan (Journal of Islamic International Medical College, 2021)
Objective: To evaluate the overall faculty performance by comparison of Self-assessment with peer and student assessment. Study Design:Acomparative cross sectional survey. Place and Duration of Study: Study was conducted from January to June 2012 in Riphah College of Rehabilitation Sciences, Riphah International University Islamabad. Materials and Methods: This research study was conducted among students of Doctor of physical therapy (DPT), post-professional Doctor of physical Therapy (PPDPT), and Master of Science in speech language pathology (MS-SLP), and faculty members at Riphah College of Rehabilitation Science (RCRS), Riphah International University Islamabad. The total sample size was 730, including 700 students and 30 faculty members. A questionnaire was developed according to likert scale, and after a pilot study on 20 student and 10 faculty member to determine the reliability. The questionnaire was circulated among all the 30 faculty members and 700 students, including 500 undergraduate and 200 post graduate students of all the 3 programs.The data was analyzed and Wilcoxon (Kruskal-Wallis) was applied at 95% level of significance for all the 3 groups. The group “A” included assessment of the performance of the faculty members done by the students, group “B” done by other faculty members, and group “C” included self assessment done by faculty members. The averages were calculated to determine the overall performance of the faculty members as assessed by themselves, other faculty members, and the by students as well, afterwards the averages of 3 groups were compared. Results: the overall performance of the faculty members was graded as 71% (P=0.015) as evaluated by the students, 77%(P=0.009) as evaluated by other faculty members, and 73% (P=0.011) as evaluated by the faculty members through self assessment. Conclusion: It is concluded that there was no significant difference in the performance of the faculty members, as assessed themselves, by the students and the other faculty members.